EFEKTIVITAS METODE PERAWATAN LUKA “MOISTURE BALANCE” TERHADAP PENYEMBUHAN LUKA PADA PASIEN ULKUS DIABETIKUM DI KLINIK PERAWATAN LUKA ISAM CAHAYA HOLISTIC CARE KOTA MAKASSAR - Rauf Harmiady; Abdul Kadir Ahmad; Karlina Ende Putri; Nasrullah Nasrullah (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2020)
ABSTRACT Wounds treatment that originally used the conventional method (dry), now switched to use the moisture balance (modern) wound treatment method, where this modern wound care uses the moist principle which aims to accelerate the process of fibrinolysis, the formation of new blood vessel capillaries (angiogenesis), reduce infection and accelerate the formation of active cells. The purpose of this study is to describe the effectiveness of the